Responses to supplementation in White Fulani cattle under agro-pastoral management in northern Nigeria. 1. Phosphorus - Campbell, D.A.; Ikuegbu, O.A.; Owen, E.; Little, D.A. (Springer, 1996)
Using on-farm supplementation trials with a P rich block (Phos) and a sult block (Salt), deficiency of P in White Fulani cattle in Nigeria was investigasted. There was some evidence, significant in some locations but nonsignificant overall, that P supplemented dans produced heavier calves and supported greater calf growth. Dam mean weight gains, 9 to 1 months pre-partum were 6.9 kg/month on Phos (s.d.=5.0, n=50) and 3.8 kg/month on Salt (s.d.=4.7 n=54) (P>0.05). Overall least squares means of calf weights at 12 months were 105.2 kg (n=29, s.e. 9.3) on Phos and 91.5 kg (n=37, s.e. 6.3) on Salt (P>0.05). In animals below 2 years of age, mortalities were 6.8 percent on Phos and 13.6 percent on Salt (n=179, Chi-square P<0.01). No response to supplementation was observed in older and non-pregnant cattle.